Aerobic Capacity Response and Hematological Profile during Performing Physical Activity at Two Public Sport Venues with Different Air Pollution Concentrations - Bahri, Samsul; Resmana, Dadan; Tomo, Haryo Satriyo; Safei, Imam; Hasan, Muhamad Fahmi (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2021)
The aim of this study was to evaluate the effect of exercise on aerobic capacity and hematological profile of amateur futsal athletes at two public sport venues having the same climatic characteristics with different air pollution concentrations. The method used in this study was a quasi experimental method with a post-test only crossover design approach. Subjects of the study were 15 futsal athletes from futsal clubs in Bandung city. The mean (SD) of age, weight, height, and BMI of the participants were 18.73 ± 1.7 years, 55.29 ± 3.0 Kg, 165.90 ± 2.6 cm, and 19.90 ± 0.8 Kg / m2. The results of this study indicated that a high amount of air pollution could significantly inhibit the increase of VO2max (p = 0.043) and hemoglobin (p = 0.023) and could significantly increase white blood cells (p = 0.042 leukocytes). The findings of this study provide evidence that air pollution can have a negative effect on the hematological profile of futsal athletes. Thus, the athlete and coach should consider the level of air pollution around the venue before doing exercise. It should be anticipated because, basically, exercising can increase the rate of air ventilation in the respiratory system so that it can cause air pollution, such as PM2.5 and PM10, entering the lungs and even the alveoli.